A broad scale model for flood simulation in the Taihu Basin, China. Issue 1 (16th October 2012) - Wicks, J.M.; Hu, C.; Scott, M.; Chen, L.; Cheng, X.
Abstract Planning for the long‐term management of flooding should be underpinned by credible evidence of current and future flood risk. Simulation of flood extents and depths is a key component of the evidence base of flood risk analysis, but flood modelling can be a time‐consuming activity. For scenario analysis studies, such as that undertaken on the Taihu Basin in China, the potentially extensive computational and staff time demands of standard flood modelling are compounded by the need for simulations of multiple futures over large areas. In this paper, we describe how a credible flood simulation method was selected and implemented for the Taihu Basin within the challenging data, resource and programme constraints. The lessons learned from the study are described and generalised to help inform modelling components of other studies, particularly broad scale analysis for flood risk management planning.